Analisis Manajemen Layanan TI pada Kebangkrutan E-commerce jd.id Menggunakan Kerangka Kerja Infrastructure Technology Information Library (ITIL v3) - Anggriani, Kurnia; Ferzha Putra Utama; Okta Piani, Sri; Vatresia, Arie; Bismantolo, Putra (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
E-commerce has recently become a place that is in great demand by consumers to shop. In general, e-commerce is a term used to describe the sale of goods and services via the internet. Among the many e-commerce services in Indonesia, one of them is JD.id. This research aims to look at the IT services used by JD.id previously by looking at the processes of domain service operations with the ITIL V3 framework and finding out the extent of management of the IT services used by JD.id before JD.id closed. The method used in this research is a quantitative descriptive method and the assessment of the results of this research is based on the answers to the questionnaire given to respondents using a Likert scale. The sample taken was 100 people who were JD.id users. The data sources obtained in this research are primary data and secondary data. The data analysis carried out was calculating the Maturity Level of the Service Operation subdomain. The results of the research obtained the lowest value, namely the problem management variable with a value of 3.70, meaning that the JD.id marketplace is still not very optimal in terms of preventing incidents from occurring and there is no permanent improvement process and is not very optimal in terms of continuous service improvement. However, the overall maturity level (Maturity Level) on average is at level 4 with a score of 3.97 this means that the IT service processes in the JD.id marketplace have been planned and implemented well and consistently, but automation with the information technology tools used is limited.